BRONCHIAL ASTHMA AND OBESITY: OPPORTUNITIES FOR INTEGRATING QUESTIONNAIRES INTO FAMILY PHYSICIAN CLINICAL PRACTICE - Лагода, Дарія; Назарян, Вероніка; Данильчук, Галина (SWorldJournal, 2025)
This study explores the impact of overweight and obesity on the course of bronchial asthma (BA) and evaluates the effectiveness of using the ACQ, AQLQ, and IWQOL-Lite questionnaires in primary healthcare settings. A total of 285 patients with BA were exam